Molecular Targets of Neurotoxic Insecticides in Apis mellifera. Issue 21 (20th April 2022) - Cens, Thierry; Chavanieu, Alain; Bertaud, Anaïs; Mokrane, Nawfel; Estaran, Sébastien; Roussel, Julien; Ménard, Claudine; De Jesus Ferreira, Marie‐Celeste; Guiramand, Janique; Thibaud, Jean‐Baptiste; Cohen‐Solal, Catherine; Rousset, Matthieu; et al.
Abstract: The intensive use of insecticides, combined with other factors such as habitat loss, might explain worldwide decrease of insect populations documented in the past twenty years. However, due to the involvement of pest species in crop destruction and in vector‐borne diseases, insecticides will probably continue to be required still for decades. The most commercially successful insecticides are neurotoxicants acting on ion channels of the central nervous system affecting thereby cellular excitability and synaptic transmission and causing insect paralysis and fatality. In this article, we provide an overview of the insecticides acting on voltage‐gated sodium channels, GABA‐gated chloride channels and nicotinic acetylcholine receptors. We summarize the current knowledge on those ion channels from the honeybee Apis mellifera and discuss the possible mode of action of neurotoxic insecticides. Abstract : Cloning of the honeybee genes encoding ion channels targeted by neurotoxic insecticides and their functional reconstitution in heterologous expression system allow the assessment of the different insecticide classes including pyrethroids and neonicotinoids. Elucidation of their mode of action, by combining electrophysiology and molecular docking, might help for the development of insecticides less harmful for beneficial insects.